Evaluation of a Contact Tracing Training Program and Field Experience - Katherine M. Strelau, BS; Nawar Naseer, PhD, MPH; Rachel Feuerstein-Simon, MPA, MPH; Kierstyn Claycomb, MS, MBA; Heather Klusaritz, PhD, MSW; Hillary C.M. Nelson, PhD, MPH; Carolyn C. Cannuscio, ScD (Elsevier, 2022)
Introduction: The study objective was to evaluate a contact tracing training program and the role of contact tracing on volunteers' professional development. Methods: A COVID-19 contact tracing program was conducted at an urban academic medical center, in collaboration with the local health department, between March 2020 and May 2021. Contact tracers, most of whom were health professions students, completed pretraining and post-training surveys to assess knowledge and self-efficacy to conduct contact tracing, plus an 18-month follow-up survey regarding career impacts. Results: We observed statistically significant post-training increases in knowledge and self-efficacy to conduct contact tracing. Contact tracers described benefiting from training regarding cultural humility, empathy, and trauma-informed interviewing. They also expressed a deeper understanding of COVID-19 inequities and their structural causes and reported that the work was emotionally demanding. Conclusions: Key to pandemic preparedness is having a trained and supported workforce. This study showed how contact tracing training and field experience strengthened students' education in the health professions by sharpening interpersonal skills and structural competency and by generating insights regarding current gaps in both public health infrastructure and support for vulnerable populations.